DEVELOPMENT OF THE INDUSTRIAL COMPLEX OF KRYVORIZHIA: ECONOMIC BENEFITS, TECHNOGENIC CONSEQUENCES AND ENVIRONMENTAL PROBLEMS - NAZARUK, Mykola; OSTROUSHKO, Maksym (Ekonomichna ta Sotsialna Geografiya, 2021)
The rapid economic development of Kryvyi Rih and large-scale geospatial changes in the territory are associated with the development of the iron ore basin and the development of the mining and industrial complex and ferrous metallurgy enterprises of the city. The study aims to highlight the positive economic factors of industrial development in the region and to study the whole complex of geospatial changes in the territory. The task of the research is also to understand the negative environmental consequences and ways to solve the problems of environmental pollution. As a result of studying historical sources and cartographic materials in the study it was possible to understand the patterns of spatial development of the city and the scale of geospatial changes in Kryvyi Rih. In the course of the work, objects of anthropogenic landscapes, water bodies and territories of industrial enterprises were studied and plotted on the city map. This made it possible to understand the peculiarities of the location, the scale of the transformation of the territory and man-made danger. The development of industry in addition to the clear economic benefits brought the city a number of environmental problems and man-made hazards such as: (1) сoncentration of potentially dangerous objects in the city (mines, quarries, dumps, sludge storages, waste cavities, etc.), which require annual discharge of excess return water; (2) formation of abysmal landscapes, which is associated with underground mining of iron ores and the displacement of adjacent blocks of native rocks; (3) the presence of waste from the extractive industry, which is presented in the form of dumps, sludge storages, heaps and landfills, forming zones of man-made desertification, the area of which by the end of the XX century. amounted to about 8% of the total territory of Ukraine; (4) emissions of pollutants into the atmosphere by the enterprises of the complex, which annually amount to more than 260 thousand tons (according to the Dnipropetrovsk regional council); (5) soil pollution as a result of industrial enterprises; (6) water pollution by heavy metals, which occurs due to discharges of insufficiently treated water by enterprises of the mining, metallurgical and metalworking industries directly into the rivers of the region.

Стрімкий економічний розвиток Криворіжжя та масштабні геопросторові зміни території пов’язані із розробкою залізорудного басейну та розбудовою гірничо-видобувного промислового комплексу і підприємств чорної металургії міста. Дослідження ставить за мету висвітлити позитивні економічні чинники розвитку промисловості регіону та вивчити весь комплекс геопросторових змін території. Також завданням дослідження є розуміння негативних екологічних наслідків та шляхів вирішення проблем забруднення навколишнього середовища. В результаті вивчення історичних джерел та картографічних матеріалів у дослідженні вдалося виявити закономірності просторового розвитку території міста та масштаби геопросторових змін Криворіжжя. В ході роботи були досліджені та нанесені на карту міста об’єкти антропогенних ландшафтів, водних об'єктів та території промислових підприємств. Це дало змогу осягнути особливості розміщення, масштаби перетворень території та техногенної небезпеки. Розвиток промисловості окрім зрозумілих економічних вигод приніс місту низку екологічних проблем та техногенних небезпек: (1) концентрація потенційно небезпечних об’єктів на території міста (шахти, кар’єри, відвали, шламосховища, відпрацьовані пустоти, тощо), які потребують щорічного скиду надлишків зворотних вод; (2) утворення провальних ландшафтів, що пов'язано з підземним видобутком залізних руд та зрушенням прилягаючих блоків корінних гірських порід; (3) наявність відходів видобувної промисловості, які представлені у вигляді відвалів, шламосховищ, териконів та звалищ, що формують зони техногенного опустелювання, площа яких до кінця XX ст. склала близько 8% від загальної території України; (4) викиди забруднюючих речовин в атмосферне повітря підприємствами комплексу, які щорічно складають понад 260 тис т (за офіційними даними Дніпропетровської обласної ради); (5) забруднення ґрунтів в результаті діяльності промислових підприємств; (6) забруднення вод важкими металами, яке відбувається через скиди недостатньо очищеної води підприємствами гірничодобувної, металургійної та металообробної промисловості безпосередньо в річки регіону.
РОЗВИТОК ПРОМИСЛОВОГО КОМПЛЕКСУ КРИВОРІЖЖЯ: ЕКОНОМІЧНІ ПЕРЕВАГИ, ТЕХНОГЕННІ НАСЛІДКИ ТА ЕКОЛОГІЧНІ ПРОБЛЕМИ
Keywords: man-made danger; mining industry; anthropogenic landscapes; quarries; stockpiles; karst landscapes; ecological condition; техногенна небезпека; гірничодобувна промисловість; антропогенні ландшафти; кар’єри; відвали; провальні ландшафти; екологічний стан